2006 IEEE Ultrasonics Symposium 2006
DOI: 10.1109/ultsym.2006.73
|View full text |Cite
|
Sign up to set email alerts
|

4C-3 Monolithically Integrated Tandem Waveguide-Type Acoustooptic Frequency Shifter Driven by Surface Acoustic Waves

Abstract: A waveguide-type acoustooptic frequency shifter (AOFS) using coplanar AO coupling due to a surface acoustic wave (SAW), that is, Bragg diffraction, in a tapered crossedchannel proton-exchanged (PE) optical waveguide on a 128 • -rotated Y-cut LiNbO3 substrate for an optical wavelength of 1.55 µm has been proposed. In this study, a monolithically integrated tandem waveguide-type AOFS driven by SAW was designed and fabricated. The structure considered was a 2×4 optical switch, in which the input ports of two seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Thus, these devices have been applied to a frequency shift feedback (FSF) fiber laser as an AO frequency shifter (AOFS). [1][2][3][4][5][6][7][8] On the other hand, recently, attention has been focused on the phase shift of a diffracted beam. Fang et al showed that a different phase shift between forward and reverse propagations can be obtained by inducing the photonic gauge potential due to photonic transitions.…”
mentioning
confidence: 99%
“…Thus, these devices have been applied to a frequency shift feedback (FSF) fiber laser as an AO frequency shifter (AOFS). [1][2][3][4][5][6][7][8] On the other hand, recently, attention has been focused on the phase shift of a diffracted beam. Fang et al showed that a different phase shift between forward and reverse propagations can be obtained by inducing the photonic gauge potential due to photonic transitions.…”
mentioning
confidence: 99%